An evidence‐base for developing ambitious yet realistic national biodiversity targets. Issue 2 (27th December 2022) - Bane, Miranda S.; Cooke, Rob; Boyd, Robin J.; Brown, Andy; Burns, Fiona; Henly, Lauren; Vanderpump, Jemilah; Isaac, Nick J. B.
Abstract: Biodiversity targets are a key tool, used at a global and national policy level, to align biodiversity goals, promote conservation action, and recover nature. Yet most biodiversity targets are not met. In England, the government has committed to legally‐binding targets to halt and recover the decline in species abundance by 2030 and 2042. We present evidence from recent population trends of 670 terrestrial animal species (for which abundance time series are available) as a species abundance indicator, together with a synthesis of case studies on species recovery, to assess the degree to which these targets are achievable. The case studies demonstrate that recovery is possible through a range of approaches. The indicator demonstrates that theoretically targets can be achieved by addressing severe declines in a relatively small number of species, as well as creating smaller benefits for many species through landscape‐scale interventions. The fact that multiple pathways exist to achieve the species abundance targets in England presents choices but also raises the possibility that targets might be reached with perverse consequences. We demonstrate that evidence on achievability is a necessary but not sufficient condition for determining what is required to deliver conservation outcomes and restore biodiversity. Abstract : For species recovery, biodiversity targets must be ambitious and realistic. Here we demonstrate how evidence‐based pathways aid the development of such targets.